Identification of potential districts for technology transfer in sesame (Sesamum indicum L.): IDENTIFICATION OF POTENTIAL DISTRICTS FOR TECHNOLOGY TRANSFER IN SESAME - M NAGAVENI; G D S KUMAR; B CHANDANA (Journal of Oilseeds Research, 2021)
India is the largest producer of sesame in the world with an area of 16.22 lakh ha and production of 6.57 lakh t and contributing to 10.5% and 11.1% ofthe Worlds’ area and production, respectively. The AICRP-sesame centres have developed location-specific improved technologies, which can enhance sesame productivity significantly, but the awareness and adoption of these technologies among farmers is very low. Hence, focused efforts are required to transfer the existing technologies from the AICRP system to the farmers’ fields through effective and efficient technology transfer programmes. To have focussed efforts for productivity enhancement and area expansion of sesame, state-wise most efficient sesame cropping districts were identified by estimating the Relative Spread Index (RSI) and Relative Yield Index (RYI). Frontline demonstrations conducted in selected districts in the most efficient, efficient, and moderately efficient districts indicated a huge yield gap and vast potential to improve the sesame productivity under real farm situations. The extension strategies to be followed in technology transfer in various categories of districts for enhancing the productivity and area expansion of sesame crop are mentioned.